Музейна комунікація як інструмент творення музею – «третього місця» - Зубар, М.В. (Сіверщина в історії України, 2020)
У статті розглядається система музейної комунікації через контекст трансформації у суспільстві. Автор аналізує потреби в музейній комунікації в сучасних умовах через потребу перегляду функцій та місця музеїв у суспільстві, у світі та в Україні. Особлива увага приділяється системі комунікації музею в широкому розумінні цього слова. Комунікація розглядається як форма діалогу з відвідувачем, у тому числі і через постійну експозицію. Робиться спроба проаналізувати концепцію «третього місця» у її відношенні до музейних інституцій. Аналізується досвід польських і європейських музеологів і висвітлюються їх підходи до трансформації музеїв відповідно до актуальних вимог сучасності. The article considers the museum communication system in the context
of transformations in society. The author analyzes the needs of rethinking
the role and place of museums in society in the new conditions,
referring to European and world experience. At that time in the w orld,
museums cease to be primarily collections of originals and become symbols
of cultural revival which defined as an element of “soft economy” and
new urbanization. In a situation where museums become institutional
features of cities and regions through which the latter improve their image
and invite tourists, the question arises of changing approaches to
organizing museum communication in Ukrainian museums in modern
conditions. It happens due to the continued crisis of museums and the
loss of their subjectivity. The museum’s communication system considered
in the broad sense - from communication with the visitor through
the exhibition and the public museum program to the use of communication
channels, social networks and new media available to museums.
Communication presented as a broad form of permanent dialogue
with the visitor. Special attention paid to the concept of “third place”
developed by Ray Oldenburg and its transformation and adaptation to
the needs and tasks of modern museums in the world. Nowadays museums
begin to be positioned not only as institutions for gaining knowledge
or aesthetic pleasure but also as a meeting place that equalizes
social statuses of people who come to the museum or remove barriers
in communication. The author analyzes the role of communication introducing
the concept of “third place” in a modern museum, exploring
the experience of Polish and European museologists. Also, covers their
approaches to the transformation of museums and museum communication
forms under the current requirements of our time.
Using Taras Shevchenko National Museum as an example, the author
demonstrates features of communication improving when museums
become one of many institutions competing in the leisure industry
for people with different levels of education and people from different
social groups.